Dampak Media Sosial dan Cara Mempromosikan Usaha Melalui Media Sosial Bagi Pedagang UMKM Pantai Sine - Pujiharti, Yulita; Lestari, Putri Ayu; Mukarom, Mukarom; Sari, Loesita (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2024)
In this modern era, social media has a big influence on our lives, we can really feel the impact of social media, especially for business promotion. UMKM are able to provide maximum contribution in maintaining the economy. However, being a small and medium enterprise does not mean it cannot provide relatively large employment opportunities because UMKM have a role in absorbing labor to reduce unemployment and contribute to expanding exports while increasing GDP or economic growth in a region. The development of increasingly modern times and the existence of open market mechanisms require UMKM to increase their competitiveness so that they can continue to operate and develop. The increasing use of the internet and the ease of internet connections is a breath of fresh air for MSMEs to be able to actively participate in keeping up with current developments via the internet, especially social media. The aim of this activity is to package a product so that it looks attractive when promoted on social media. After following the tips and strategies that have been explained, Sine Beach UMKM traders can promote their businesses effectively through social media Tiktok.